European Law and New Health Technologies - Flear, Mark L; Farrell, Anne-Maree; Hervey, Tamara K; Murphy, Thérèse (Oxford Studies in European Law, 2013)
Health is a matter of fundamental importance in European societies, both as a human right in itself, and as a factor in a productive workforce and therefore a healthy economy. New health technologies promise improved quality of life for patients suffering from a range of diseases, and the potential for the prevention of incidence of disease in the future. At the same time, new health technologies pose significant challenges for governments, particularly in relation to ensuring the technologies are safe, effective, and provide appropriate value for (public) money. To guard against the possible dangers arising from new health technologies, and to maximize the benefits, all European governments regulate their development, marketing, and public financing. In addition, several international institutions operating at European level, in particular the European Union, the Council of Europe, and the European Patent Office, have become involved in the regulation of new health technologies. They have done so both through traditional 'command and control' legal measures, and through other regulatory mechanisms, including guidelines, soft law, 'steering' through redistribution of resources, and private or quasi-private regulation. This collection analyses European law and its relationships with new health technologies. It uses interdisciplinary insights, particularly from law but also drawing on regulation theory, and science and technology studies, to shed new light on some of the key defining features of the relationships and especially the roles of risk, rights, ethics, and markets. The collection explores the way in which European law's engagement with new health technologies is to be legitimized, and discusses the implications for biological or biomedical citizenship.